2012
DOI: 10.1021/jp2121774
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Vibrational Spectroscopy of [FeFe]-Hydrogenase Model Compounds

Abstract: Model compounds have been found to structurally mimic the catalytic hydrogen-producing active site of Fe-Fe hydrogenases and are being explored as functional models. The time-dependent behavior of Fe(2)(μ-S(2)C(3)H(6))(CO)(6) and Fe(2)(μ-S(2)C(2)H(4))(CO)(6) is reviewed and new ultrafast UV- and visible-excitation/IR-probe measurements of the carbonyl stretching region are presented. Ground-state and excited-state electronic and vibrational properties of Fe(2)(μ-S(2)C(3)H(6))(CO)(6) were studied with density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 81 publications
11
66
1
Order By: Relevance
“…21,22,24,31 The faster timescale was widely attributed to electronic relaxation or cooling of vibrationally hot species 22, 32 while the longer timescale was attributed to the geminate recombination of species that have undergone CO photolysis upon photoexcitation. [20][21][22][23][24][25] This model is broadly consistent with the data observed here.…”
Section: Trir Spectroscopysupporting
confidence: 88%
See 2 more Smart Citations
“…21,22,24,31 The faster timescale was widely attributed to electronic relaxation or cooling of vibrationally hot species 22, 32 while the longer timescale was attributed to the geminate recombination of species that have undergone CO photolysis upon photoexcitation. [20][21][22][23][24][25] This model is broadly consistent with the data observed here.…”
Section: Trir Spectroscopysupporting
confidence: 88%
“…These included species arising from CO-loss, which would be expected to be present based on previous studies of the photochemistry of hydrogenase sub-site analogues and is further indicated by the similar dynamics for the TRIR peak recovery reported above to previous work on similar systems. [20][21][22][23][24][25] Ground state carbonyl ligand dissociation energies were calculated to be 40, 47 and 57 kcal/mol for the CO ap , CO eq and CO dppv ligands respectively, in reasonably good agreement with the TD-DFT results reported previously (45, 51 and 58 kcal/mol, respectively). 14 It is noteworthy that the available photon energies at 335, 490 and 572 nm are 85, 58 and 50 kcal/mol, respectively, suggesting that, even at the longest wavelength studied, CO dissociation is by no means prohibited, though it may be approaching the limit at which it is possible for the CO dppv ligand at longer wavelengths.…”
Section: Dft Calculations Of Photoproduct Speciessupporting
confidence: 81%
See 1 more Smart Citation
“…With 355 nm excitation, an additional photoproduct consisting of electronic excitation accompanied by a longer Fe-Fe bond is observed. Using 532 nm excitation, both pathways are still observed, but the electronic excitation is significantly stronger [43]. Similar dynamics are seen in 1b but with significantly more spectral overlap between the two photoproducts.…”
Section: Introductionmentioning
confidence: 83%
“…Ultrafast time-resolved, UV-visible pump, IR probe spectroscopy (TRIR) was previously performed by our group on 1a , 1b , and 2a by exciting the sample at multiple wavelengths [43, 44]. These studies utilized 532 nm, 355 nm, and 266 nm excitation wavelengths which correspond to absorptions in the UV-visible spectra of these models.…”
Section: Introductionmentioning
confidence: 99%